Super-tensile strong-adhesion quasi-dual-network conductive hydrogel as well as preparation method and application thereof

By introducing a quasi-dual network structure with ion bridge-hydrogen bond synergy into the hydrogel, the problem of achieving ultra-high tensile strength and stable conductive pathways in hydrogels under high water content conditions is solved, achieving high adhesion and stable electrical properties on multiple substrates, which is suitable for flexible wearable sensors and bioelectronic devices.

CN121135945APending Publication Date: 2025-12-16ZHAOQING BAOJUN CHEM CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511401668.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-28
Publication Date
2025-12-16

AI Technical Summary

Technical Problem

Existing hydrogels struggle to simultaneously achieve ultra-high tensile strength, stable conductive pathways, and strong adhesion to multiple substrates under high water content conditions. Furthermore, they exhibit insufficient conductive response drift and cyclic stability under large strain, and poor electromechanical performance at low temperatures.

Method used

Employing a quasi-dual network structure without external conductive fillers or under high-salt conditions, and through ion bridge-hydrogen bond synergy, a quasi-dual network conductive hydrogel formed by polyols and zwitterionic monomers is achieved, resulting in high water content, ultra-large tensile strength, and stable electrical response.

Benefits of technology

Achieving a balance between high water content, ultra-high tensile strength, and stable electrical response within a single material system, maintaining high adhesion and repeatable adhesive-peel properties on multiple substrates, adapting to low temperature and dry environments, and suitable for flexible wearable sensors and bioelectronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121135945A_ABST
    Figure CN121135945A_ABST
Patent Text Reader

Abstract

The invention discloses a super-tensile strong-adhesion quasi-dual-network conductive hydrogel as well as a preparation method and application thereof. The super-tensile strong-adhesion quasi-dual-network conductive hydrogel is characterized in that a zwitterionic monomer and a hydrophilic monomer are polymerized to form a first phase domain, a conductive polymer is used as a second phase domain, the second phase domain is semi-interpenetrated in the first phase domain in a coil / micelle state, and meanwhile, a second ionic cross-linked network is formed; and the second ionic cross-linked network accounts for 3.3 to 33.3 wt% of the quasi-dual-network conductive hydrogel network. According to the quasi-dual-network conductive hydrogel provided by the invention, under the condition of no additional conductive filler or high salt, through an ion bridge-hydrogen bond synergetic quasi-dual-network structure, consideration of high water content, super-large stretching and stable electrical response is realized at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of soft matter and functional polymer materials, and particularly relates to a super-stretching and strong-adhesion quasi-dual-network conductive hydrogel as well as a preparation method and application thereof. BACKGROUND

[0002] Hydrogels are widely used in flexible wearable sensors, bioelectrodes and tissue engineering due to their high water content and good biocompatibility. However, under the premise of high water content, it is still a challenge to simultaneously achieve i) ultra-high stretch and high energy dissipation, ii) continuous and stable conductive paths under large deformation, and iii) strong adhesion to various solid and wet tissue surfaces. The existing approaches to improve conductivity often rely on conductive fillers (carbon nanomaterials, metal nanoparticles) or high salt / ionic liquids, which often lead to unbalanced mechanical and conductive properties, migration and salt precipitation, and insufficient long-term stability.

[0003] In the direction of conductive polymers, PEDOT:PSS contains a flexible conjugated main chain and a sulfonate side group, and has water dispersing processing and electrochemical stability, and has been used in hydrogel electrodes or composite hydrogels. CN113466304A discloses a PEDOT:PSS hydrogel modified electrode; ZL 202210198550.3 discloses a kind of PVA / PEDOT:PSS dual-network conductive hydrogel, which has high mechanical strength but limited stretch rate, and does not focus on the ion bridge coordination mechanism of zwitterionic network; ZL 202010641956.5 discloses a kind of dual-network conductive hydrogel formed by combining chitosan quaternary ammonium salt / cellulose and PEDOT:PSS, which relies on strong chemical crosslinking and a process of adjusting pH by post-processing.

[0004] In summary, the existing technology generally has the following problems: i) relying on additional nanofillers or strong crosslinking leads to difficulty in balancing toughness and electrical conductivity; ii) insufficient conductive response drift and cycle stability at large strain scales (1000%); iii) limited in-situ strong adhesion to multiple substrates such as skin / metal / ceramic / wet tissue; iv) insufficient electrical-mechanical performance retention in low temperature / dry environment; iv) lack of equivalent ratio engineering and gradient structure design based on zwitterionic-conductive polymer ion bridge reversible association. It is urgent to solve the above problems. SUMMARY

[0005] The purpose of the present application is to provide a super-stretching and strong-adhesion quasi-dual-network conductive hydrogel as well as a preparation method and application thereof. The quasi-dual-network conductive hydrogel proposed by the present application simultaneously realizes high water content, ultra-high stretch and stable electrical response through ion bridge-hydrogen bond coordinated quasi-dual-network structure without additional conductive fillers or high salt conditions.

[0006] The present application is realized by the following technical solutions:

[0007] A preparation method of a super-stretching strong-adhesion quasi-dual-network conductive hydrogel, comprising the following steps:

[0008] (1) adding zwitterionic monomer, hydrophilic monomer, crosslinking agent and photoinitiator into deionized water in sequence, dissolving and mixing uniformly to obtain a first phase solution, then slowly adding a second phase solution into the first phase solution, mixing uniformly and preliminarily defoaming to obtain a gel precursor solution;

[0009] (2) placing the gel precursor solution obtained in step (1) under vacuum condition for defoaming treatment to remove residual bubbles in the system; then uniformly pouring it into a pre-prepared mold cavity and sealing, then performing light curing under specific wavelength light irradiation condition through a patterned photomask to make the gel form a pre-designed patterned structure; finally, standing at room temperature and demolding to obtain the quasi-dual-network conductive hydrogel.

[0010] Preferably, the zwitterionic monomer in step (1) is selected from one or more of carboxybetaine methacrylamide (CBMAA), sulfobetaine methacrylate (SBMA), carboxybetaine acrylamide (CBAA), divinylbenzyl propane sulfonic acid ammonium salt (SVBA), sulfobetaine methacrylamide (SBMAA) and 2-methacryloyloxyethyl phosphorylcholine (MPC); the hydrophilic monomer is selected from one or more of 2-hydroxypropyl methacrylate (HPMA), N-(2-hydroxyethyl) acrylamide (HEAA), acrylamide (AAm), 2-hydroxyethyl acrylate (HEA), 2-hydroxyethyl methacrylate (HEMA) and acrylic acid (AAc); the crosslinking agent is selected from one of N,N'-methylenebisacrylamide (MBAA), poly(ethylene glycol) diacrylate (PEGDA) and N,N'-bisacryloyl cystamine (BAC); and the photoinitiator is selected from one of hydroxy-4'-(2-hydroxyethoxy)-2-methylpropanoyl phenone (Irgacure 2959) and lithium phenyl-2,4,6-trimethylbenzoyl phosphinate (LAP).

[0011] Preferably, the mass ratio of the hydrophilic monomer to the zwitterionic monomer is 4-29:1, the mass ratio of the zwitterionic monomer to the photoinitiator is 5-30:1, the mass ratio of the zwitterionic monomer to the crosslinking agent is 1-60:1, and the mass-volume ratio of the hydrophilic monomer to deionized water is 2.4-2.9:3 g / mL.

[0012] Further preferably, the mass ratio of the hydrophilic monomer to the zwitterionic monomer is 6.5-14.0:1, the mass ratio of the zwitterionic monomer to the photoinitiator is 2.5-10.0:1, the mass ratio of the zwitterionic monomer to the crosslinking agent is 3.3-20.0:1, and the mass-volume ratio of the hydrophilic monomer to deionized water is 2.6-2.8:3 g / mL.

[0013] The gel precursor solution also includes an antifreeze-anti-drying agent, which is a polyol, specifically ethylene glycol and / or glycerol, and is added at a rate of 0-25 wt% of the zwitterionic monomer, based on the mass of the zwitterionic monomer.

[0014] Preferably, the second phase domain solution in step (1) is a conductive polymer solution, wherein the conductive polymer is selected from one of poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS), polyaniline (PANI), and polypyrrole (PPy), and the solvent of the conductive polymer solution is selected from one or more of water and polyols, wherein the polyol is ethylene glycol and / or glycerol, the solid content of the conductive polymer solution is 0.2-1.5 wt%, and the molar ratio of zwitterionic monomer to conductive polymer dopant ions is 15-60:1.

[0015] Further preferred, the conductive polymer solution is a PEDOT:PSS aqueous dispersion with a solid content of 1.3wt% and a mass-to-volume ratio of hydrophilic monomer to PEDOT:PSS aqueous dispersion of 2.6:0.1-0.5g / mL.

[0016] Preferably, the photocuring conditions in step (2) are: wavelength 254-405 nm, power 5-50 mW·cm⁻¹ -2 The curing time is 1-6 hours.

[0017] Further preferred, the photocuring conditions in step (2) are: wavelength 365nm, power 10mW·cm⁻¹. -2 The curing time is 1.5 hours.

[0018] Preferably, the quasi-dual-network conductive hydrogel can achieve the formation of various preset patterned structures with the assistance of a photomask template. The patterned structures include, but are not limited to, striped, dotted, honeycomb, grid, and gradient distributed patterns.

[0019] The present invention also protects the super-stretched, strongly adhesive quasi-dual-network conductive hydrogel obtained by the above preparation method, wherein a first phase domain is formed by the polymerization of zwitterionic monomers and hydrophilic monomers, and a conductive polymer serves as a second phase domain. The second phase domain is semi-interpenetrating in the first phase domain in a coil / micelle state, and simultaneously forms a second ionic crosslinking network. The second ionic crosslinking network accounts for 3.3-33.3 wt% of the quasi-dual-network conductive hydrogel network.

[0020] Preferably, the conductive polymer network accounts for about 6.7-13.3 wt% of the conductive hydrogel network.

[0021] The quasi-dual-network hydrogel proposed in this invention achieves high water content, super-stretching (≥1000% to ≥4000%), and stable electrical response in a single material system under conditions without added conductive fillers or high salt. It maintains continuous conductive pathways and reduces ΔR / R0 drift under ultra-large deformation (>1000%) and multiple cyclic loading (>10 times). It achieves high adhesion and repeatable adhesion-peel behavior on multiple substrates such as glass / metal / ceramic / skin / wet tissue. It improves the retention rate of electromechanical performance under low temperature (freezing resistance) and dry (drying resistance) environments. It provides a scalable and patternable (gradient / anisotropic / microgel neck) process and parameter window, which facilitates large-scale preparation and integrated device assembly.

[0022] The super-stretchable, strongly adhesive quasi-dual-network conductive hydrogel proposed in this invention exhibits an elongation at break ≥1000% (preferably ≥4000%), a tensile strength of 0.1-1.0 MPa, and a toughness ≥700 J·m at a 90° peel interface with multiple substrates. -2 (Preferred ≥1500 J·m) -2 The signal is stable during 900% strain cycles.

[0023] like Figure 1 As shown, taking PEDOT:PSS as an example, PSS-SO3- is reversibly associated with the positively charged centers (quaternary ammonium / betaine / pyridinium) of the zwitterionic network, and multi-point hydrogen bonds and hydrophobic stacking are superimposed to form a distributed "conductive pathway"; the pathway self-reconstructs without breaking under strain.

[0024] Polyols are used to resist freezing and drying; stepwise / mask photocuring achieves a thickness-direction PEDOT:PSS enrichment gradient; pre-formed microgels are then cured in a secondary manner to form a "conductive bridge".

[0025] This invention also protects the application of the aforementioned highly tensile and adhesive quasi-dual-network conductive hydrogel in flexible wearable sensors, bioelectronic interfaces, soft robots, bioelectronic devices, or flexible electronic devices. Specifically, it includes: use as a controllable adhesive in flexible wearable sensors, as a tissue adhesion medium in bioelectronic interfaces, as an adjustable adhesion layer in soft robot grasping or motion units, and in other biological or flexible electronic devices requiring both conductivity and high adhesion.

[0026] Compared with the prior art, the beneficial effects of the present invention are:

[0027] 1. The quasi-dual network conductive hydrogel proposed in this invention achieves a balance between high water content, ultra-large tensile strength, and stable electrical response through a quasi-dual network structure with ion bridge-hydrogen bond synergy, without the addition of external conductive fillers or under high salt conditions.

[0028] 2. This invention enables distributed conductive pathways to self-reconstruct without breaking under large deformation by using an equivalent ratio window and PEDOT:PSS semi-interpenetration, significantly reducing cyclic ΔR / R0 drift.

[0029] 3. This invention utilizes the multi-point ion / hydrogen bonding of zwitterionic networks and combines a thickness-direction PEDOT:PSS enrichment gradient design to achieve high adhesion and repeatable adhesion-peel performance on multiple substrates such as glass, metal, ceramics and wet tissues.

[0030] 4. This invention utilizes the synergistic water-fixing mechanism of diols / polyols and zwitterionic sites to maintain ≥70% of the initial comprehensive electrical and mechanical properties under cycling conditions of -20 to 60°C.

[0031] 5. This invention employs a microgel-"neck bridge" strategy and mask / stepwise photopolymerization to achieve patterned and anisotropic structures, facilitating large-scale manufacturing and integrated device assembly.

[0032] 6. This invention constructs a distributed conductive pathway with ion-bridge coupling within a single material system, which is more conducive to industrial implementation. Attached Figure Description

[0033] Figure 1 This is a schematic diagram of the quasi-dual-network structure and mechanism of the quasi-dual-network conductive hydrogel of the present invention, showing the ion bridge / hydrogen bond coupling and distributed conductive pathway between the zwitterionic-hydrophilic copolymer network (first phase domain) and the semi-interpenetrating PEDOT:PSS (second phase domain).

[0034] Figure 2 The quasi-double network preparation process of the quasi-double network conductive hydrogel of the present invention is as follows: a one-pot two-step method (dissolution → degassing → photocuring) and an optional mask gradient structure curing scheme.

[0035] Figure 3 Typical mechanical and electrical property curves of the conductive hydrogel in Example 1: stress-strain curve and ΔR / R0 strain response under multiple cycles of loading / unloading under 1200% tensile strain condition.

[0036] Figure 4 This is a schematic diagram of the multi-substrate adhesion test of the quasi-dual-network conductive hydrogel obtained in Example 1: 90° peel / interface toughness test diagram on glass, metal, ceramic and wet tissue substrates.

[0037] Figure 5 This is a schematic diagram of the device structure in Example 1. Detailed Implementation

[0038] The present invention will be further described in detail below with reference to the embodiments. These embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Experimental methods in the following embodiments that do not specify specific conditions are generally performed under conventional conditions in the art or as recommended by the manufacturer; the raw materials and reagents used, unless otherwise specified, are considered to be commercially available materials and reagents that can be obtained through conventional markets and other commercial channels.

[0039] Example 1

[0040] like Figure 2 As shown, 3 mL of deionized water was added to a clean container, and 2.60 g of HPMA (2-hydroxypropyl methacrylate), 0.40 g of CBMAA (carboxybenzene methacrylamide), 0.06 g of LAP (lithium phenyl-2,4,6-trimethylbenzoylphosphonate), and 0.03 g of crosslinking agent MBAA were dissolved sequentially. The mixture was magnetically stirred for 10 min until clear. Then, 0.50 mL of PEDOT:PSS dispersion (1.3 wt% solids) was slowly added dropwise, and stirring was continued for 5 min. Subsequently, the mixture was vortexed / sonicated for 10 min to thoroughly mix and preliminarily defoam, obtaining a gel precursor solution. The gel precursor solution was defoamed under vacuum for 3 min, poured into a 1.0 mm thick silicone mold cavity, and sealed with a PET film. A 365 nm light source (10 mW·cm⁻¹) was used. -2 Irradiate for 1.5 hours (5-10 cm from the light source). After curing, allow to stand at room temperature for 5 minutes before demolding to obtain a quasi-double network conductive hydrogel with a thickness of approximately 1.0 mm.

[0041] The resulting quasi-double-network conductive hydrogel exhibits excellent mechanical properties. Under standard tensile test conditions (tensile rate of 50 mm·min), -1 The dumbbell-shaped specimen has an elongation at break of ≥4000%, which is much higher than that of conventional conductive hydrogels; at the same time, it maintains a tensile strength of 0.4-0.5MPa, combining high ductility and structural stability.

[0042] Multi-substrate adhesion: In a 90° peel test on glass / aluminum / titanium substrates, the interfacial toughness was approximately 1500 J·m. -2 (50mm·min -1 (Sample width 15mm).

[0043] Electrical stability: such as Figure 3 As shown, after 10 cycles at 1000% strain, ΔR / R0 remained stable and the curves showed good overlap.

[0044] Self-healing properties: It closes within 3-10 minutes after being cut in air at room temperature, and its strength recovers by about 30% after self-healing.

[0045] Application instructions: such as Figure 4As shown, the quasi-dual-network conductive hydrogel can be directly adhered to substrates such as skin (wet pigskin tissue), titanium, ceramics, and glass, making it suitable for the sensitive layer of strain / pressure sensing elements.

[0046] like Figure 5 As shown, quasi-dual-network conductive hydrogel is used as an adhesive for flexible wearable sensors. The device structure is a sandwich structure consisting of a copper / carbon flexible electrode, a fabricated quasi-dual-network conductive hydrogel sensitive layer, and an encapsulation film.

[0047] Example 2

[0048] Add 3 mL of deionized water to a clean container, and dissolve 3.00 g HPMA, 0.06 g LAP, and 0.03 g MBAA sequentially. Stir magnetically for 10 min until clear. Unlike Example 1, this example does not include the zwitterionic monomer CBMAA. Then, slowly add 0.50 mL of LPEDOT:PSS dispersion (1.3 wt% solids) and continue stirring for 5 min. The solution is then subjected to a combined vortex / ultrasonic treatment for 10 min to obtain a homogeneous gel precursor solution. The resulting solution is degassed under vacuum, poured into a 1.0 mm thick silicone mold cavity, and irradiated with a 365 nm light source for 1.5 h. After curing, allow to stand at room temperature for 5 min before demolding to obtain a conductive hydrogel with a thickness of approximately 1.0 mm.

[0049] Mechanical properties: Under standard tensile test conditions (same as above), its elongation at break drops to about 800-1200%, which is much lower than that of Example 1 (≥4000%); the tensile strength is only 0.15-0.2 MPa, showing obvious ductility and insufficient strength.

[0050] Multi-substrate adhesion: In a 90° peel test on a glass / aluminum / titanium substrate, the interfacial toughness decreased to approximately 600 J·m. -2 Compared to Example 1, the amount of adhesive residue decreased by approximately 60%, indicating significant adhesion deficiency.

[0051] Electrical performance: During cyclic testing at 1000% strain, ΔR / R0 showed severe drift, and the curves could not be superimposed, indicating a loss of electrical stability.

[0052] Self-healing properties: After cutting, the sample cannot be effectively closed at room temperature and has almost no recoverable strength.

[0053] Application Notes: The hydrogel obtained in this embodiment is difficult to maintain a stable conductive path under large deformations and lacks sufficient interfacial adhesion and environmental adaptability. Therefore, it is not suitable for applications such as flexible sensing, bioelectronics, or tissue adhesion. Compared with Example 1, this fully demonstrates the key role of zwitterionic monomers in constructing the "ion bridge synergistic network".

[0054] Example 3

[0055] Add 3 mL of deionized water to a clean container, and dissolve 2.60 g HPMA, 0.40 g CBMAA, 0.06 g LAP, and 0.03 g MBAA sequentially. Stir magnetically for 10 min until clear. Then add 0.50 mL of polyaniline (PANI) aqueous solution (solid content approximately 1.0 wt%) and continue stirring for 5 min. After vortexing / ultrasonic treatment for 10 min, a homogeneous gel precursor solution is obtained. The resulting solution is degassed under vacuum, poured into a 1.0 mm thick silicone mold cavity, and irradiated with a 365 nm light source for 1.5 h. After curing, allow to stand at room temperature for 5 min before demolding to obtain a conductive hydrogel with a thickness of approximately 1.0 mm.

[0056] Mechanical properties: Under standard tensile test conditions (same as above), its elongation at break is only 600-800%, and its tensile strength is about 0.15-0.18 MPa. It shows that its overall mechanical properties are weak and not significantly better than conventional single-network hydrogels.

[0057] Electrical properties: The initial conductivity is high, showing strong conductivity; however, in the cyclic test under large strain (>500%), the ΔR / R0 curve drifts significantly, and the stability is significantly weaker than that of the PEDOT:PSS reference sample, indicating that its conductive path is not stable enough under deformation conditions.

[0058] Multi-substrate adhesion: In 90° peel tests on glass / metal / ceramic substrates, the interfacial toughness is approximately 1100-1300 J·m. -2 It is superior to Example 2 and exhibits better interface adhesion.

[0059] Self-healing properties: After cutting, the sample partially closes at room temperature, but the recovery rate is less than 10%, and it has almost no effective self-healing function.

[0060] Application Notes: This PANI-based conductive hydrogel exhibits strong electrical conductivity, but its weak mechanical properties and insufficient electrical stability limit its long-term application in high-strain flexible electronic devices. Although it shows good in-situ adhesion to various substrates, it still lacks the balance between toughness and cycling stability compared to the PEDOT:PSS-based system.

[0061] Example 4

[0062] Add 3 mL of deionized water to a clean container, and dissolve 2.60 g HPMA, 0.40 g CBMAA, 0.06 g LAP, and 0.03 g MBAA sequentially. Stir magnetically for 10 min until clear. Then, slowly add 0.10 mL of PEDOT:PSS dispersion (1.3 wt% solids, approximately 1 / 5 of the amount used in Example 1), and continue stirring for 5 min. The solution is then subjected to a combined vortex / ultrasonic treatment for 10 min to obtain a homogeneous gel precursor solution. After degassing under vacuum, the solution is poured into a 1.0 mm thick silicone mold cavity, covered with a PET film, and irradiated with a 365 nm light source for 1.5 h. After curing, allow to stand at room temperature for 5 min before demolding to obtain a conductive hydrogel with a thickness of approximately 1.0 mm.

[0063] Mechanical properties: Under standard tensile test conditions, the elongation at break was only 500%-700%, which was a sharp decrease compared to Example 1; the tensile strength remained at 0.35-0.40 MPa, which was lower than that of Example 1 but not significantly; the overall modulus did not decrease, showing a trend towards brittleness.

[0064] Electrical performance: The initial conductivity was significantly lower than that of Example 1, and the ΔR / R0 curve drifted significantly when cyclically subjected to 300%-500% strain, indicating a severe weakening of electrical stability.

[0065] Multi-substrate adhesion: In the 90° peel test on glass / metal / ceramic substrates, the interfacial toughness decreased to approximately 700-900 J·m. -2 It is only about half of that in Example 1.

[0066] Self-healing properties: The cut sample can hardly close effectively, and the strength recovery rate is less than 5%.

[0067] Application Notes: The drastic decrease in PEDOT:PSS content led to a significant decline in the electrical properties and elongation at break of the hydrogel, while the tensile modulus did not decrease accordingly. This highlights the crucial role of the equisional ratio engineering and gradient structure design of the reversible association of "zwitterionic-conductive polymer ion bridges" in the system. When the ion bridge ratio is severely unbalanced, the network cannot form an effective dynamic synergistic support structure, resulting in the loss of the "flexibility-conductivity" coupling characteristics. Compared with Example 1, this further highlights the unique technical route of this invention, which achieves high strength, toughness, and stable conductivity by optimizing the equisional ion bridge ratio and constructing a gradient network structure.

[0068] Example 5

[0069] Add 3 mL of deionized water to a clean container, and dissolve 2.60 g HPMA, 0.40 g CBMAA, 0.06 g LAP, and 0.03 g MBAA sequentially. Stir magnetically for 10 min until clear. Then add 2.00 mL of PEDOT:PSS dispersion (1.3 wt% solids) all at once and continue stirring for 5 min. At this point, the solution is clearly dark and highly viscous. After vortexing / ultrasonic treatment for 10 min, large-area phase separation and uneven distribution still exist in the system. The obtained precursor solution is degassed under vacuum and poured into a 1.0 mm thick silicone mold cavity, and irradiated with a 365 nm light source for 1.5 h. After curing, it was found that the sample surface exhibited sagging and stratification, and could not form a complete self-supporting hydrogel, presenting as a semi-cured viscous mass.

[0070] Gelation properties: It failed to form a stable and continuous three-dimensional gel network. The sample as a whole was a fragile gel-liquid mixture and lacked shape retention ability.

[0071] Mechanical properties: Due to the inability to effectively form a gel, standard tensile testing cannot be performed.

[0072] Electrical properties: High initial conductivity, but the overall structure of the sample is unstable, resulting in poor electrode contact and signal drift during measurement, making it impossible to obtain effective cycle stability data.

[0073] Multi-substrate adhesion: The peel test could not be completed due to adhesive failure.

[0074] Application Notes: Excessive use of PEDOT:PSS will severely disrupt the dynamic balance of the "zwitterionic-conductive polymer ion bridge," preventing the polymer main network from effectively cross-linking and molding. Too much PEDOT:PSS is equivalent to oversaturation of the "ion bridge," causing phase separation and non-uniform microregions within the network, ultimately leading to overall gelation failure. This comparative result further emphasizes the necessity of the "equivalent proportioning engineering and gradient structure design" proposed in this invention: only under reasonable proportions can the reversible association between PEDOT:PSS and zwitterionic monomers synergistically achieve a balance of "toughness, conductivity, and gelling properties" (quasi-double network).

[0075] Example 6

[0076] Based on Example 1, the obtained gel precursor solution was "patterned" before molding. The specific steps are as follows:

[0077] First, the vacuum-degassed gel precursor solution (formulation same as in Example 1) was injected into a silicone mold pre-prepared with a microstructure pattern. The inner wall of the mold contained regularly distributed striped / matrix-like microgrooves (depth 50-100 μm, spacing 100-200 μm), forming a periodic pattern structure. The mold was then sealed with a PET film and cured using a 365 nm light source for 1.5 h. After demolding, a conductive hydrogel with a microstructure pattern distributed on both the surface and interior was obtained.

[0078] Mechanical properties: Under standard tensile test conditions, the elongation at break remained at 2800%-3200%, slightly lower than in Example 1, but the tensile strength increased to 0.55-0.60 MPa, showing a good balance between strength and ductility.

[0079] Multi-substrate adhesion properties: In a 90° peel test on glass / aluminum / titanium substrates, the interfacial toughness increased to 1800-2000 J·m. -2 The improvement is about 20%-30% compared to Example 1. This is because the patterned structure effectively disperses stress, increases the contact area, and induces a synergistic effect between the soft and hard phases.

[0080] Electrical properties: The initial conductivity is comparable to that of Example 1; in the cyclic test at 1000% strain, the ΔR / R0 curves show good overlap and the electrical stability is not negatively affected.

[0081] Self-healing properties: After cutting, the tissue closes at room temperature for 5-10 minutes, and the strength recovery rate is about 25%-30%, which is similar to that of Example 1.

[0082] Application Description: Patterned modulation, by introducing periodic microstructures, induces a more balanced spatial distribution of "soft segments (hydrophilic zwitterionic networks)" and "hard segments (PEDOT:PSS enriched regions)," thereby achieving synergistic optimization of mechanical and adhesive properties. This design can further expand the application potential of the system of this invention in wearable flexible electronics, skin-adhesive sensors, and highly adhesive bioelectronic interfaces.

[0083] Example 7

[0084] Based on Example 1, the vacuum-degassed gel precursor solution (formulation same as Example 1) was poured into a 1.0 mm thick silicone mold cavity and covered with a PET film. Unlike the uniform illumination of Example 1, this example used a photomask with striped / lattice microstructures (transparent area width 100-200 μm, spacing 50-150 μm) for selective curing under 365 nm light source for 1.5 h. After removing the photomask, the gel was irradiated again for 0.5 h. Due to the mask blocking light intensity in some areas, a quasi-dual-network conductive hydrogel with a periodic "soft segment / hard segment" distribution was finally obtained.

[0085] Mechanical properties: Under standard tensile test conditions, the elongation at break is about 2500%-3000%, and the tensile strength is increased to 0.56-0.62MPa, indicating that the regional curing induced by the photolithography mask makes the network hard segments more concentrated, thereby improving the strength.

[0086] Multi-substrate adhesion properties: In a 90° peel test on glass / metal / ceramic substrates, the interfacial toughness is approximately 1600-1700 J·m. -2 Similar to Example 1, but exhibits more stable adhesion under dynamic peeling conditions (high strain rate).

[0087] Electrical performance: The overall initial conductivity is close to that of Example 1; in the cyclic test at 1500% strain, the ΔR / R0 curves still overlap well, indicating that the photomask did not significantly weaken the electrical stability, but may have formed a "conductive neck".

[0088] Self-healing performance: After cutting, the self-healing rate is about 20%-25% when the wound closes at room temperature for 5-10 minutes. This is slightly lower than that of Example 1, but it is still practical.

[0089] Application Description: This embodiment controls the photocuring area using a photolithographic mask, achieving spatial distribution of network hard / soft segments. This improves tensile strength and modulus while maintaining ductility. This "mask-induced structural design" can be used in scenarios requiring localized reinforcement, such as joint areas in flexible electronic devices that need to simultaneously meet high strength and flexible fit requirements.

[0090] Example 8

[0091] Based on Example 1, the zwitterionic monomer CBMAA was replaced with an equimolar amount of SVBA, while keeping other raw material ratios and operating procedures unchanged: 3 mL of deionized water was added to a clean container, and 2.60 g of HPMA, 0.40 g of SVBA, 0.06 g of LAP, and 0.03 g of MBAA were dissolved sequentially, and the mixture was magnetically stirred for 10 min until clear. Then, 0.50 mL of PEDOT:PSS dispersion was slowly added dropwise, and stirring continued for 5 min. The mixture was then subjected to a vortex / ultrasonic treatment for 10 min to obtain a homogeneous gel precursor solution. After degassing, the resulting solution was poured into a 1.0 mm thick silicone mold cavity, covered with a PET film, and irradiated with a 365 nm light source for 1.5 h. After curing, the solution was demolded to obtain a conductive hydrogel.

[0092] Mechanical properties: Under standard tensile test conditions, the elongation at break decreased to 1200%-1600%, and the tensile strength was approximately 0.20-0.25 MPa, exhibiting overall brittleness. The modulus increased slightly, indicating that the system's rigidity was enhanced but its toughness was insufficient.

[0093] Multi-substrate adhesion properties: In a 90° peel test on glass / metal / ceramic substrates, the interfacial toughness is approximately 800-1000 J·m. -2 It is only about half of that in Example 1.

[0094] Electrical properties: The initial conductivity is slightly lower than that of Example 1; in the cyclic test at 600% strain, the ΔR / R0 curve drifts significantly, indicating poor stability of the conductive path.

[0095] Self-healing properties: The ability to close at room temperature after cutting is extremely weak, with a recovery rate of less than 10%, and it basically does not have effective self-healing properties.

[0096] Application Notes: Introducing styrene-based rigid zwitterionic monomers significantly weakens the dynamic reversibility of the "zwitterionic-conductive polymer ionic bridge." Because the rigid benzene ring skeleton restricts chain segment flexibility, the ionic groups struggle to establish a stable dynamic association network with PEDOT:PSS, resulting in a significant decrease in mechanical toughness, interfacial adhesion, and electrical stability.

[0097] Example 9

[0098] Based on Example 1, an additional 0.20 mL of glycerol or ethylene glycol (either optional) was introduced into the gel precursor solution formulation, while maintaining the same raw material ratios and operating steps: 2.60 g HPMA, 0.40 g CBMAA, 0.06 g LAP, and 0.03 g MBAA were dissolved sequentially in 3 mL of deionized water, magnetically stirred for 10 min until clear, then 0.50 mL of LPEDOT:PSS dispersion and 0.20 mL of glycerol (or ethylene glycol) were slowly added dropwise, and stirring continued for 5 min. After vortexing / ultrasonic treatment for 10 min, a homogeneous gel precursor solution was obtained. The resulting solution was degassed under vacuum and poured into a 1.0 mm thick silicone mold cavity, then cured by irradiation with a 365 nm light source for 1.5 h; after demolding, a quasi-double-network conductive hydrogel was obtained.

[0099] Mechanical properties: Under standard tensile test conditions, the elongation at break is significantly increased to 5500%-6000%, far exceeding that of Example 1; the tensile strength decreases to 0.25-0.30 MPa, and the modulus decreases by about 30%-40%, exhibiting more flexible rather than rigid mechanical properties.

[0100] Anti-drying properties: After standing for 48 hours at room temperature and 30% relative humidity, the hydrogel volume retention rate reaches 85-90%, which is better than 60%-65% in Example 1.

[0101] Freeze resistance: After freezing at -20℃ for 12 hours, the sample still maintains its flexibility and shows no obvious brittleness. After returning to room temperature, it can be stretched back to more than 4000%.

[0102] Electrical performance: The initial conductivity is slightly lower than that of Example 1 (a decrease of about 10%-15%). In the cyclic test at 1000% strain, the ΔR / R0 curves still overlap well, indicating that the electrical stability is not seriously affected.

[0103] Multi-substrate adhesion properties: interfacial toughness remains at 1400-1500 J·m -2 It is close to the level of Example 1.

[0104] Application Notes: By introducing low-molecular-weight polyols (glycerol or ethylene glycol), this hydrogel achieves excellent anti-drying and anti-freezing properties, maintaining flexibility and conductivity even in extreme environments. Although tensile strength and modulus decrease, the significantly increased elongation (to 6000%), along with good interfacial adhesion and environmental adaptability, makes it exhibit superior overall performance in flexible sensors, wearable devices, and long-term bioelectronic interfaces in cold environments.

[0105] Example 10

[0106] Based on Example 1, the zwitterionic monomer CBMAA was replaced with an equal amount of SBMA, while keeping other raw material ratios and operating procedures unchanged: 2.60 g HEAA, 0.40 g SBMA, 0.06 g LAP, and 0.03 g MBAA were dissolved sequentially in 3 mL of deionized water and magnetically stirred for 10 min until clear. Then, 0.50 mL of PEDOT:PSS dispersion was slowly added dropwise, and stirring continued for 5 min. The mixture was then subjected to a vortex / ultrasonic treatment for 10 min to obtain a homogeneous gel precursor solution. The resulting solution was degassed under vacuum and poured into a 1.0 mm thick silicone mold cavity, covered with a PET film, and cured by irradiation with a 365 nm light source for 1.5 h. After standing at room temperature for 5 min, the mixture was demolded to obtain a quasi-double-network conductive hydrogel.

[0107] Mechanical properties: Under standard tensile conditions, the elongation at break reaches 3000-3800%, which is slightly lower than that of Example 1, but still maintains a high degree of ductility far exceeding that of conventional conductive hydrogels; the tensile strength is maintained at 0.35-0.45 MPa, and the modulus is close to that of Example 1.

[0108] Multi-substrate adhesion properties: In the 90° peel test on glass / metal / ceramic substrates, the interfacial toughness is 1300-1600 J·m. -2 Similar to Example 1, it exhibits excellent adhesion properties.

[0109] Electrical performance: After 8 cycles at 1000% strain, the ΔR / R0 curves overlapped well, indicating that the electrical stability was comparable to that of Example 1.

[0110] Self-healing properties: After cutting, the wound closes at room temperature in 5-10 minutes, and the strength recovery rate after self-healing is about 20-25%, maintaining a similar level to Example 1.

[0111] Application Notes: When the zwitterionic monomer is replaced with SBMA instead of CBMAA, a stable synergistic network can still be constructed through the "zwitterionic-PEDOT:PSS ion bridge," achieving high ductility, excellent adhesion, and cyclic electrical stability. Compared to Example 1, its performance shows only a slight decrease, further verifying that flexible betaine-based zwitterionic monomers are suitable for the system of this invention, thus supporting the protection scope of this invention for a broad group of zwitterionic monomers.

[0112] Example 11

[0113] Add 3 mL of deionized water to a clean container and dissolve 2.40 g HEAA, 0.60 g SBMA, 0.12 g LAP, and 0.06 g MBAA sequentially. Stir magnetically for 10 min until clear. Slowly add conductive polymer PEDOT:PSS dispersion (0.2 wt% solids) and 0.1 mL ethylene glycol, and continue stirring for 5 min. Then, perform vortexing / ultrasonic treatment for 10 min to thoroughly mix and initially defoam, obtaining a gel precursor solution. After defoaming under vacuum, the resulting solution is poured into a 1.0 mm thick silicone mold cavity, covered with a PET film, and irradiated with a 365 nm light source for 1.5 h. After curing, allow to stand at room temperature for 5 min before demolding to obtain a conductive hydrogel with a thickness of approximately 1.0 mm.

[0114] Mechanical properties: Due to the relatively high amount of crosslinking agent, the gel network is relatively dense, resulting in insufficient overall flexibility. Under standard tensile test conditions, the elongation at break is only in the range of 300%-500%, which is much lower than that of Example 1; although the tensile strength remains at 0.5-0.6 MPa, the sample exhibits obvious brittle fracture characteristics.

[0115] Conductivity: The PEDOT:PSS incorporation is extremely low (only 0.2 wt% solids), and it is difficult to form an effective and continuous conductive path in the highly cross-linked dense network, resulting in a significant decrease in overall conductivity. Under the same test conditions, the hydrogel exhibits higher resistance and larger fluctuations in the ΔR / R0 curve under tensile deformation, with poor repeatability, indicating poor conductivity.

[0116] Adhesion properties: When subjected to a 90° peel test on substrates such as glass and aluminum sheets, the interfacial toughness is approximately 600-800 J·m. -2 The result was lower than in Example 1, mainly because the gel was too rigid and the interface mismatch led to a weakening of the peeling resistance.

[0117] Self-healing properties: Due to the high density of chemical cross-linking and the limited number of free segments, the ability to re-entangle / recombine after cutting is poor. After being cut in air at room temperature, the self-healing strength recovery is less than 20% within 10 minutes, which is far lower than that of the control sample.

[0118] Application Notes: This quasi-dual-network conductive hydrogel has a certain degree of moldability in its structure, but its poor conductivity and brittle mechanical properties limit its application potential in flexible sensors and wearable devices. It is more suitable for scenarios with low strain and non-critical electrical response.

[0119] Example 12

[0120] Add 3 mL of deionized water to a clean container, and dissolve 2.90 g of hydrophilic monomers HEAA, 0.10 g of SBMA, 0.005 g of LAP, and 0.0017 g of MBAA sequentially. Stir magnetically for 10 min until clear. Slowly add PEDOT:PSS dispersion (1.5 wt% solids) and 0.1 mL of glycerol, and continue stirring for 5 min. Then, perform vortexing / ultrasonic treatment for 10 min to thoroughly mix and initially defoam, obtaining a gel precursor solution. After defoaming under vacuum, the resulting solution is poured into a 1.0 mm thick silicone mold cavity, covered with a PET film, and irradiated with a 365 nm light source for 1.5 h. After curing, allow to stand at room temperature for 5 min before demolding to obtain a conductive hydrogel with a thickness of approximately 1.0 mm.

[0121] Mechanical properties: Due to the high PEDOT:PSS content, the dispersion itself is acidic, which somewhat damages the stability of the gel network, leading to the failure of some crosslinking points and a decrease in the overall strength of the gel. In the standard tensile test, the breaking strength is only 0.15-0.20 MPa, lower than that of Example 1, but the elongation at break can be increased to 4500%-5000%, exhibiting ultra-high ductility.

[0122] Conductivity: With a high PEDOT:PSS doping level, a relatively continuous conductive pathway is formed within the gel, significantly reducing resistance and noticeably improving overall conductivity. In cyclic testing at 1000% strain, the ΔR / R0 variation is relatively stable, but due to decreased network mechanical stability, electrical reproducibility slightly decreases over long cycles.

[0123] Adhesion properties: The system is soft and has a high water content, allowing for a large contact area with various substrates. In a 90° peel test on a glass / titanium substrate, the interfacial toughness remained at 1200-1400 J·m. -2 .

[0124] Self-healing properties: The acidic environment weakens some intermolecular hydrogen and ionic bonds, but the lower crosslinking density provides higher degrees of freedom for the chain segments. After cutting at room temperature, the chain closes within 5-8 minutes, and its strength recovers to approximately 30%-35% after self-healing.

[0125] Application Notes: This hydrogel also has high ductility and excellent conductivity, making it particularly suitable for applications such as large deformation strain sensors and flexible electronic patches; however, due to the decrease in mechanical strength, stability needs to be improved through composite or secondary structure optimization in high-strength load-bearing applications.

[0126] The above description of the embodiments is only for the purpose of helping to understand the technical solution and core idea of ​​the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principle of the present invention, and these improvements and modifications also fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a super-stretched, strongly adhesive quasi-dual-network conductive hydrogel, characterized in that, Includes the following steps: (1) Add zwitterionic monomer, hydrophilic monomer, crosslinking agent and photoinitiator to deionized water in sequence, dissolve and mix evenly to obtain a first phase domain solution, and then slowly add a second phase domain solution to the first phase domain solution to make it fully mixed and initially defoamed to obtain a gel precursor solution. (2) The gel precursor solution obtained in step (1) is placed under vacuum to degas the system in order to remove residual bubbles. The gel is then poured evenly into a pre-prepared mold cavity and sealed. It is then photocured under specific wavelength light conditions using a photomask template with a set pattern, so that the gel forms a pre-designed patterned structure. Finally, it is allowed to stand at room temperature and then demolded to obtain the quasi-dual-network conductive hydrogel.

2. The preparation method according to claim 1, characterized in that, The zwitterionic monomer in step (1) is selected from one or more of carboxybetaine methacrylamide, sulfobetaine methacrylate, carboxybetaine acrylamide, divinylbenzylpropane sulfonate ammonium salt, sulfobetaine methacrylamide, and 2-methacryloyloxyethyl phosphorylcholine; the hydrophilic monomer is selected from one or more of 2-hydroxypropyl methacrylate, N-(2-hydroxyethyl)acrylamide, acrylamide, 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, and acrylic acid; the crosslinking agent is selected from one of N,N'-methylenebisacrylamide, poly(ethylene glycol) diacrylate, and N,N'-bisacryloylcysteine; the photoinitiator is selected from one of hydroxy-4′-(2-hydroxyethoxy)-2-methylpropionyl phenyl ketone and lithium phenyl-2,4,6-trimethylbenzoylphosphonate.

3. The preparation method according to claim 1 or 2, characterized in that, The mass ratio of hydrophilic monomer to zwitterionic monomer is 4-29:1, the mass ratio of zwitterionic monomer to photoinitiator is 5-20:1, the mass ratio of zwitterionic monomer to crosslinking agent is 10-60:1, and the mass-volume ratio of hydrophilic monomer to deionized water is 2.4-2.9:3 g / mL.

4. The preparation method according to claim 1 or 2, characterized in that, The second phase domain solution mentioned in step (1) is a conductive polymer solution. The solvent of the conductive polymer solution is selected from one or more of water and polyols. The polyol is ethylene glycol and / or glycerol. The conductive polymer is selected from one of poly(3,4-ethylenedioxythiophene):polystyrene sulfonate, polyaniline and polypyrrole. The solid content of the conductive polymer solution is 0.2-1.5 wt%, and the molar ratio of zwitterionic monomer to conductive polymer dopant ions is 15-60:

1.

5. The preparation method according to claim 1 or 2, characterized in that, The photocuring conditions described in step (2) are: wavelength 254-405nm, power 5-50mW·cm. -2 The curing time is 1-6 hours.

6. The preparation method according to claim 1, characterized in that, The quasi-dual-network conductive hydrogel can achieve the formation of various pre-defined patterned structures with the assistance of a photomask template. The patterned structures include, but are not limited to, striped, dot-matrix, honeycomb, grid, and gradient distributed patterns.

7. The super-stretched, strongly adhesive quasi-dual-network conductive hydrogel obtained by the preparation method of claim 1, characterized in that, The first phase domain is formed by the polymerization of zwitterionic monomers and hydrophilic monomers, and the conductive polymer serves as the second phase domain. The second phase domain is semi-interpenetrating in the first phase domain in the form of coils / micelles, and at the same time forms a second ionic cross-linked network. The second ionic cross-linked network accounts for 3.3-33.3 wt% of the quasi-dual network conductive hydrogel network.

8. The application of the quasi-dual-network conductive hydrogel of claim 7 in flexible wearable sensors, bioelectronic interfaces, soft robots, bioelectronic devices or flexible electronic devices.

Citation Information

Patent Citations

  • Preparation of double-network conductive hydrogel and application of double-network conductive hydrogel in strain sensor

    CN111763334A

  • PEDOT: PSS hydrogel modified electrode and preparation method and application thereof

    CN113466304A

  • Dual-network conductive hydrogel and preparation method thereof

    CN114716718A